The relationship between work productivity performance and variations in acute responses / Nurhayati binti Mohd Nur - Mohd Nur, Nurhayati (2015)
High work productivity is typically associated with hard production standard times. Even though hard production standards generally result in higher work productivity, the tasks become more repetitive and workers may be exposed to higher rates of acute responses which will lead to higher risks of contracting work-related musculoskeletal disorders (WMSDs). The main objective of this study is to investigate the relationship between work productivity, acute responses and WMSD risks at various levels of production standard time. Muscle activity, muscle fatigue and energy expenditure are selected as the physiological acute responses, whereas perceived muscle fatigue is selected as the psychological acute response. The methodology adopted in this study comprises an industrial survey and a series of experimental tasks. A total of 288 workers participate in the industrial survey (automotive manufacturing industry) while 20 workers are recruited for the experimental tasks. The results of the industrial survey reveal that 76.0% of the workers experienced WMSD symptoms at various regions of the body. The overall work impairment due to WMSD symptoms is determined to be 22.28%. The experimental results reveal that muscle activity increases by roughly a factor of two as the production standard time shifts from hard to very hard (PS3: 6.9%, PS4: 12.9%). The Extensor Carpi Radialis-Left muscle exhibits the highest muscle activity. The muscle fatigue rate is found to be higher for hard and very hard production standard times (PS3: 0.105, PS4: 0.115). In addition, the energy expenditure increases significantly for hard and very hard production standard times (PS3: 15.5%, PS4: 32.5%). The results are supported by the higher rate of perceived muscle fatigue obtained for both hard and very hard production standard times (PS3: 3.8, PS4: 4.9). In summary, higher acute responses indicate a higher risk of contracting WMSDs as well as a decline in work productivity performance for hard and very hard production standard times (PS3: <3% (123%), PS4: <11% (129%)). A regression model is developed specifically to predict work productivity based on the strong correlation and linear relationship between muscle activity, perceived muscle fatigue, production standard time and work productivity (R = 0.784). There is also a strong correlation and linear relationship between muscle activity, energy expenditure and production standard time (R = 0.868). Furthermore, a regression model which predicts energy expenditure in terms of the maximum task intensity is developed in this study. The regression models are validated using data from a different set of industrial workers. To conclude, a new approach which integrates acute responses with task time analysis has been devised to assess the productivity of workers in the manufacturing industry. Major contributing findings from this study are the development of two regression models, which predicts the work productivity and maximum task intensity of workers, respectively. The findings of this study are highly beneficial to the automotive manufacturing industry as a guideline to sustain work productivity among workers to fulfil the ever-increasing demands of the industry while minimizing the risk of contracting WMSDs.